2020
DOI: 10.1136/bmjopen-2019-036067
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of lung ultrasonography in the hands of non-imaging specialists to diagnose and assess the severity of community-acquired pneumonia in adults: a systematic review

Abstract: ObjectivesWe aimed to systematically review the published literature regarding adults with clinical suspicion of pneumonia that compares the accuracy of lung ultrasonography (LUS) performed by non-imaging specialists to other reference standards in diagnosing and evaluating the severity of community-acquired pneumonia. Moreover, we aimed to describe LUS training and the speciality of the physician performing LUS, time spent on the LUS procedure and potential harms to patients.Materials and methodsWe searched M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
0
13
0
4
Order By: Relevance
“…(Ndege et al 2020) Poor standardization of skills POCUS is now rapidly being adopted by non-radiologist clinicians. Many studies therefore compare the skills of the clinician with that of the radiologist and often show encouraging outcomes (Strøm et al 2020). These results, however, do not guarantee safe POCUS practices.…”
Section: Lack Of Trials Showing An Impactmentioning
confidence: 99%
“…(Ndege et al 2020) Poor standardization of skills POCUS is now rapidly being adopted by non-radiologist clinicians. Many studies therefore compare the skills of the clinician with that of the radiologist and often show encouraging outcomes (Strøm et al 2020). These results, however, do not guarantee safe POCUS practices.…”
Section: Lack Of Trials Showing An Impactmentioning
confidence: 99%
“…The Emergency Medical Technicians (EMTs) and paramedics (PMs) are in charge of the management including initial evaluation, treatment, and making decisions regarding time spend on the scene, transport, and location [7]. Most often, the decisions are based on patient history, vital signs, and few objective examinations like auscultation [6,8,9]. Making ultrasound available for the EMTs and PMs creates a new option for assessment of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus regarding the amount of training or level of competence needed to perform LUS [80]. A systematic review found a limited number of high-quality studies about LUS training and recommended further research with validated theoretical and practical tests for assessment [81].…”
Section: Lus Training Needsmentioning
confidence: 99%